Recent Extreme Precipitation and Temperature Changes in Djibouti City (1966–2011). (8th December 2013) - Ozer, Pierre; Mahamoud, Ayan
Abstract : A dataset of 23 derived indicators has been compiled to clarify whether the frequency of rainfall and temperature extremes has changed over the last decades in Djibouti City, eastern Africa. Results show that all precipitation indices have declined over the last decades, although only the very wet day frequency and the very wet day proportion present a significant decline. Annual total precipitation has decreased by 17.4% per decade from 1980 to 2011 and recent mean yearly rainfall (44 mm on average from 2007 to 2011) meets a 73% deficit compared to the 30-year (1981–2010) average (164 mm). The average temperature increase is +0.28°C per decade.Extremely warm days (maximum temperature ≥45.0°C) have become 15 times more frequent than in the pastwhile extremely cool nights (minimum temperature ≤8.6°C) have almost disappeared. Current rainfall shortages and increasing temperature extremes are impacting local people who urgently need adaptation strategies.